Transcatheter Closure of Atrial Septal Defect in a Patient with Cor Triatriatum Sinister and Atrial Septal Defect - Wasana Hongkan; Kriangsak Thongchaiprasit; Kritvikrom Durongpisitkul (Case Reports in Cardiology)
Cor triatriatum sinister is a rare congenital heart disease and rarely found in adults. The authors describe an asymptomatic 20-year old man presenting with heart murmur by check up. Transthoracic and transesophageal echocardiogram demonstrate atrial septal defect (ASD) secundum 26 mm and cor triatriatum sinister with 20 mm of fenestration. Transcatheter closure of ASD using Occlutech FigullaR device was successfully performed without complications. Echocardiogram post procedure demonstrate good position of device without obstruction of blood flow, no residual shunt and residual 12 mm of fenestration of cor triatriatum.